Strategies in Creating a Learning Climate in the Classroom - Raihul Jannah; Sulastri; Ainun Anggriani; Rangga Siswanto; Wawan Setiawan; Bisman Al Fahrezi; Muji Gurrahman (Edumaspul: Jurnal Pendidikan, 2026)
The classroom learning climate is a crucial factor in determining the success of the educational process. A conducive classroom atmosphere can increase student motivation, participation, and learning outcomes. However, in practice, various problems are still encountered, such as low student discipline, lack of motivation to learn, monotonous learning methods, and unsupportive classroom physical conditions. This paper aims to examine strategies that teachers can employ to create a comfortable, active, and enjoyable learning climate. The method used is a literature review, analyzing various sources related to classroom management and learning. The results of the study indicate that teachers play a central role in building a classroom climate through warm communication, the use of a variety of learning methods, appropriate classroom physical design, the application of positive discipline, and providing motivation and rewards to students. Furthermore, the use of icebreakers and emotional approaches has also proven effective in increasing student engagement. With the appropriate and consistent implementation of strategies, a conducive learning climate can be created, optimally supporting students’ academic, social, and emotional development. Abstrak Iklim pembelajaran dalam kelas merupakan faktor penting yang menentukan keberhasilan proses pendidikan. Suasana kelas yang kondusif mampu meningkatkan motivasi, partisipasi, serta hasil belajar peserta didik. Namun, dalam praktiknya masih ditemukan berbagai permasalahan seperti rendahnya disiplin siswa, kurangnya motivasi belajar, metode pembelajaran yang monoton, serta kondisi fisik kelas yang kurang mendukung. Penulisan ini bertujuan untuk mengkaji strategi yang dapat dilakukan guru dalam menciptakan iklim pembelajaran yang nyaman, aktif, dan menyenangkan. Metode yang digunakan adalah studi literatur dengan menganalisis berbagai sumber terkait manajemen kelas dan pembelajaran. Hasil kajian menunjukkan bahwa guru memiliki peran sentral dalam membangun iklim kelas melalui komunikasi yang hangat, penggunaan metode pembelajaran yang variatif, penataan lingkungan fisik kelas yang baik, penerapan disiplin positif, serta pemberian motivasi dan penghargaan kepada siswa. Selain itu, penggunaan ice breaking dan pendekatan emosional juga terbukti efektif dalam meningkatkan keterlibatan siswa. Dengan penerapan strategi yang tepat dan konsisten, iklim pembelajaran yang kondusif dapat terwujud sehingga mampu mendukung perkembangan akademik, sosial, dan emosional peserta didik secara optimal.